Pengaruh Karakteristik Individu, Pengembangan Karir, dan Kualitas Sumber Daya Manusia terhadap Kinerja Karyawan : Studi Kasus pada Karyawan PT. Prima Vista Solusi Regional Tangerang - Alvian Dedi Saputra; Widi Wahyudi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study was conducted to analyze and examine the influence of individual characteristics, career development, and the quality of human resources on employee performance at PT. Prima Vista Solusi using a quantitative approach through a survey method. Data were collected by distributing questionnaires to 70 respondents who are employees and were analyzed using multiple linear regression with the assistance of SPSS software. The results show that individual characteristics and the quality of human resources have a significant effect on improving employee performance, while the career development variable does not have a significant effect on performance. This indicates that although the career development system has been well implemented, it has not yet become a primary factor in improving performance. Therefore, the company is advised to place greater focus on human resource management policies aimed at enhancing employees’ competencies, skills, and professionalism so that performance can be continuously improved in a sustainable manner.